Engineering of β-mannanase from Aspergillus niger to increase product selectivity towards medium chain length mannooligosaccharides - Arunrattanamook, Nattapol; Wansuksri, Rungtiva; Uengwetwanit, Tanaporn; Champreda, Verawat (Journal of bioscience and bioengineering, 2020)
Mannooligosaccharides (MOSs) are one of the most commonly used biomass-derived feed additives. The effectiveness of MOS varies with the length of oligosaccharides, medium length MOSs such as mannotetraose and mannopentaose being the most efficient. This study aims at improving specificity of β-mannanase from Aspergillus niger toward the desirable product size through rational-based enzyme engineering. Tyr 42 and Tyr 132 were mutated to Gly to extend the substrate binding site, allowing higher molecular weight MOS to non-catalytically bind to the enzyme. Hydrolysis product content was analyzed by high-performance anion-exchange chromatography with pulsed amperometric detection. Instead of mannobiose, the enzyme variants yielded mannotriose and mannotetraose as the major products, followed by mannobiose and mannopentaose. Overall, 42% improvement in production yield of highly active mannotetraose and mannopentaose was achieved. This validates the use of engineered β-mannanase to selectively produce larger MOS, making them promising candidates for large-scale MOS enzymatic production process. •Aspergillus niger mannanase (ManF3) was engineered to modify product specificity.•Based on rational design, ManF3Y42G and ManF3Y132G were constructed and assayed.•Mannotetraose was the major hydrolysis product from the variant enzymes.•Yield of MOSs with medium size, mannotetraose and mannopentaose, has been increased by 42%.